EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Kusrini Kusrini; Supriyadi Supriyadi; Syamsul Bahri; Ivylentine Datu Palittin; Mitra Rahayu; Helga A. Silubun; Martha Loupatty (Musamus Journal of Science Education, 2018)
This study aims to describe the application of the Discovery Learning learning model assisted by Powerpoint media to students of class X IPA 3 of SMA Negeri 2 Merauke in improving the results of physics learning. This type of research is PTK using a descriptive approach consisting of 2 cycles. Based on the results of this study, it can be concluded that discovery learning learning models make students able to become more active and motivated to find their own solutions to the problems faced. The use of powerpoint media that displays moving images also makes learning more interesting. This is evidenced by an increase in scores at the end of each cycle. To increase the enthusiasm of students, then at the end of the cycle an award is given in the form of congratulations to students or groups that excel. Keywords: Media Powerpoint, Discovery Learning, Learning Outcomes